The Nyangahant Ritual In The Culture Of Salako Community At Kampung Pueh Lundu, Sarawak - Alexander, Chelum; Mohamad Maulana, Magiman; Mangai, Tugau; Mohd Saufi, -; Semsolbahri, Bokhari; Norhuda, Salleh (Science Research Society, 2021)
This research is about the Nyangahantritual in the culture of the Salako community in Kampung Pueh, Lundu, Sarawak.The Nyangahant ritual isthe main ritual in the culture of the Salakocommunity. To ensure that the rituals performed achieve the purpose and goal, the Nyangahantritual must be performed according to the prescribedprocess. The situation is for the purpose of perfection to assure that the wish requestedcan be accepted by Jubata, the god of the Salako community. The main focus of this research is to identify themeaning of every ritual performed in the Nyangahantritual in the Salako community. This study uses ethnographic methods for data collection using an ethnographic interview technique that involvesthe informants who are experts on Nyangahantritual ceremonies,which areTuha Adat, Nyangahant craftsmen, headman,and village chief.In addition, observation methods are also widely used in this research to deeply understand the ritual ceremonies of Nyangahantin the studiedcommunity. The observation techniques areconductedbefore, during,and after the Nyangahantritual ceremony. This study found that the Nyangahantritual ceremony is the ‘mother’of all rituals for the Salakocommunity. It became a priority in the executed ritual or other festivals. Moreover, the ritual also a prayer in the prayingceremony toask for well-being and prosperity spared from all problems, calamities,and misfortune. Although the culture and customs of the Salakocommunity have evolved mainly through the process of modernity in terms of heritage, they still held the ritual as a lifeline in their community.